Information Genome, the Genomes of Individual and Population - Rubikas, Jonas (Problemos, 2002)
The genetic information is encoded in the DNA nucleotide sequence. It is necessary to distinguish two concepts: DNA molecule (or its fragment) as a chemical substance and DNA molecule as a carrier of genetic information. The main difference between them consists in the expression of the information. In the DNA millions of nucleotide long molecule there is encoded cellular, organism and population information. Information genome is the DNA or RNA molecule carrying information for the beginning of replication (plasmid), for the replication of enzymes and other proteins and structures connected with the replication (viruses). Such genomes replicate only inside the cell. The genome of individual contains the information for the autonomous life in the environment. The population genome is the
Keywords: genetinė informacija; genomas; DNR; individas; populiacija